Socio-productive dynamics in agricultural systems. Conceptual theoretical bases for the study - Albornoz, Arlenis (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
Agricultural production systems are very dynamic, the use and combination of production factors by the farmer is reflected in different levels of production and family well-being. The objective of this article was to build a theoretical - conceptual reflection, for a multiple, interdisciplinary and transdisciplinary approach in the interpretation of phenomena that are not caused exclusively by one factor. For this, a systematic bibliographic review of documents hosted on Google Scholar/Google was carried out, which allowed analyzing and comparing concepts and theories associated with the topic, highlighting Bertalanffy’s systems theory, Morín’s complexity and Lonergan’s economic dynamics. In addition, concepts associated with the research such as productivity, agricultural systems, territory and family well-being were considered. The search yielded fifty-eight documents, which were subjected to filters for pre-established exclusions. As a result of these filters, eighteen were selected for analysis, which allowed the construction of a theoretical-conceptual body for the study and analysis of socio-productive dynamics in agricultural systems, which focuses on how the inputs represented by the producer, capital, Information and agricultural inputs are related to each other and interact with other factors such as local technology, workforce, territory, environment and marketing and how these generate different levels of performance, productivity and well-being in the system for the farmer and his family.